IMF Staff papers : Volume 5 No. 1. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1956)
This paper discusses impact of purchasing power on deferred payments. The importance of the economic consequences for the economy of the adoption of purchasing power guarantees would, of course, depend on the range within which these guarantees were applied. Any practical proposals are therefore predicated on the assumption that, for the country in question, there is uncertainty about future general price movements. The problem which purchasing power guarantees are intended to solve is shown in its simplest form in the settlement of a private debt. In countries suffering from inflation, the improvement in the lender-borrower relationship would also be strengthened, since, with a purchasing power clause in the contract, the stigma of usury that would attach to any attempt to insist on high nominal rates of interest in order to ensure a proper real return would be avoided. The legal and social sanctions against usury in money terms give rise to a paradox in discussing the use of a purchasing power clause. The analytical discussion seems to show that, if anything, the borrower would gain more than the lender from the use of the clause-simply because interest payments are likely to be larger relative to his net income, and to have their real value stabilized would have a greater stabilizing effect on real income.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet